Exploring Multicultural Family Dynamics: An Analysis of Family Dysfunction in Mochtar Lubis's Senja di Jakarta - Mafi Sri Wahyu Tiara; Ahmad Bahtiar (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Sumatera Barat, 2024)
The characters representing couples and the familial system portrayed in Mochtar Lubis's novel "Senja di Jakarta" exhibit forms of family dysfunction that should ideally be characterized by a sense of comfort and security. This is demonstrated through the relationships constructed by the characters within various households. As this issue evolves, the researcher became interested in conducting a study with the hope that future generations could better understand the significance of family and how familial roles can be appropriately and effectively fulfilled. The families depicted through the characters in the novel face various issues that serve as primary factors contributing to family dysfunction. Among these primary factors are a lack of communication, minimal understanding and care among family members, and the normalization of prioritizing one's own thoughts over those of others. This research examines the forms of family dysfunction in Mochtar Lubis's novel "Senja di Jakarta," utilizing a literary sociology approach by employing William J. Goode's family sociology theory. Forms of dysfunction are influenced by significant changes resulting from the emergence of new values within a family; the breakdown of relationships is considered a social issue for individuals or couples, leading to feelings of fear and apprehension towards marriage. The concept of a fragmented family portrays a form of familial disunity and emotional unsupportiveness among its members. Additionally, the absence of one partner due to unwanted circumstances and the failure of undesired significant roles represent two forms of family dysfunction that occur beyond control and directly impact family sustainability. This research is expected to contribute significantly to a deeper understanding of familial issues, particularly within literary works such as novels. A qualitative method was employed in this study, emphasizing textual facts that were subsequently examined, understood, categorized, and analyzed based on forms of family dysfunction.